(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
The aim of the present work was exploring the effective utilization of nickel converter slag by means of the methodology of pressure oxidative leaching. The central composite design of response surface methodology was employed to optimize controlling conditions for leaching more valuable metals such as nickel, cobalt and copper, while dissolution of iron was curbed. XRD, SEM-EDS were performed for characterizing the structure of leach residues for analyzing the mechanism of selective leaching. Experimental results demonstrate that the effects of temperature and sulfuric acid concentration on the metals extraction and filtration rate are significant, followed by liquid/solid (L/S) ratio. The optimized conditions for leaching the converter slag is: temperature 208 °C, sulfuric acid concentration 0.35 mol/L and L/S ratio 5.4 mL/g. Under the above conditions, 99.60% Co, 99.20% Ni and 96.80% Cu are extracted into solution together with only 0.21% Fe, and the filtration rate of leach slurry arrives 576.86 L∙m‒2∙h‒1. The mechanism for achieving selective leaching nickel, cobalt and copper against iron dissolution and good filtration performance of the leach slurry is letting iron dissolved in the solution decomposed and hydrolyzed mainly to form hematite (α-Fe2O3 and γ-Fe2O3) and letting silicic acid formed precipitated SiO2 in the leach residue.